White fang - London, Jack, 1876-1916 ([Boston, Mass] : Thomson Heinle, 2007)
The adventures in the northern wilderness of a dog who is part wolf and how he comes to make his peace with man. Includes extensive illustrations with captions providing background information
Title from container
Keywords: American fiction -- 20th century; Dogs -- Fiction; Human-animal relationships -- Juvenile fiction; Wolves -- Fiction